2019
DOI: 10.1111/1365-2664.13416
|View full text |Cite
|
Sign up to set email alerts
|

Grazing‐induced patchiness, not grazing intensity, drives plant diversity in European low‐input pastures

Abstract: 1. Livestock grazing at low stocking rates is widely recommended to maintain grassland biodiversity. However, empirical evidence of grazing-intensity effects on plant diversity is contradictory. Explicitly considering the small-scale heterogeneity of short, frequently grazed and tall, rarely grazed patches typical of low-input grazing systems may be crucial to the understanding of paddock-scale grazing effects.2. We studied three patch types (short, intermediate, tall) within an unfertilised long-term cattle g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 52 publications
4
19
0
Order By: Relevance
“…This became particularly apparent in autumn and shows that the shorter day length is a serious limitation when the need for selection is great. The creation of patches as a compensatory measure, which was frequently observed in more suitable plant associations (Distel et al 1995;Tonn et al 2019), did not work as hoped here. This can probably be attributed to the inadequate suitability of sedges: they are only bitten in the upper leaf areas, which does not lead to young shoots.…”
Section: Synthesismentioning
confidence: 76%
See 1 more Smart Citation
“…This became particularly apparent in autumn and shows that the shorter day length is a serious limitation when the need for selection is great. The creation of patches as a compensatory measure, which was frequently observed in more suitable plant associations (Distel et al 1995;Tonn et al 2019), did not work as hoped here. This can probably be attributed to the inadequate suitability of sedges: they are only bitten in the upper leaf areas, which does not lead to young shoots.…”
Section: Synthesismentioning
confidence: 76%
“…Nevertheless, the compatibility of extensive beef production with the promotion of biodiversity while at the same time conserving soil and water resources remains a major economic challenge. Forage selection of grazing cattle and associated space use are at the core of this challenge for two reasons: on the one hand, because the forage selection success is decisive for the individual animal performance (Breitsameter et al 2017) and thus for the economic efficiency of land use, and on the other hand, because the heterogeneity pattern in vegetation created by selective grazing is a prerequisite for a high level of biodiversity (Tonn et al 2019). Therefore, the following sections deal with the spatial and temporal processes necessary to understand the interaction between herbage selection and the generation of animal performance.…”
Section: Suitability Of Extensive Cattle Grazing For a Sustainable Mamentioning
confidence: 99%
“…Further studies showed that within grazing intensities, the botanical composition differed between short and tall patches as a consequence of modified resource availability for light and soil nutrients ( 4 ). Tonn et al ( 11 ) observed larger phytodiversity in short patches compared to tall ones, and Perotti et al ( 29 ) found that species in tall patches had higher competitiveness and the ones in short patches higher stress tolerance according to the competitor, stress tolerator, ruderal (CSR) theory after Grime ( 30 ).…”
Section: Methodsmentioning
confidence: 99%
“…Patch grazing is characterized by a pronounced spatial heterogeneity in forage intake ( 9 ) with intensive and extensive grassland utilization occurring in close proximity within the same pasture. Several studies in semi-natural grassland found that the productivity ( 10 ), soil nutrient contents ( 10 , 11 ), and the vegetation composition ( 4 , 12 ) are driven by these temporally stable patches ( 7 ) rather than by the pasture-scale grazing intensity. The extent of patch grazing is controlled by the pasture stocking rate, i.e., the herbage allowance per grazing animal.…”
Section: Introductionmentioning
confidence: 99%
“…Bartha et al, 2014;Merriam et al, 2018;Mangano et al, 2019), as well as on the impact of shifts in the management type and its intensity (e.g. Köhler et al, 2005;Doležal et al, 2018;Tonn et al, 2019). Recently, a great emphasis is placed on the examination of ecological mechanisms shaping the community composition (see review in Mudrák et al, 2019), and thus on the exploration of the community assembly rules (Maire et al, 2012;Hedberg et al, 2014).…”
Section: Introductionmentioning
confidence: 99%